Green Finance and Renewable Energy in Emerging Markets: Exploring the Roles of Financial Development - Epor, Simon Okaja; Akande, Joseph Olorunfemi (International Journal of Energy Economics and Policy, 2025)
The high economic potential of emerging economies is expected to experience a surge in energy demand owing to high economic activity. This increase is closely linked to population growth and rising per capita energy consumption, as shown in advanced countries. However, this trend is likely to lead to environmental degradation with reliance on fossil fuels, whose use has a devastating impact on living conditions through the environment. This is the scenario that makes the renewable energy option more appropriate. The study mainly examined how green finance affected renewable energy in 21 emerging economies from 2010 to 2022, taking into consideration the different structures of financial development, markets, and institutions. The empirical results showed that both TSLS and FMOLS analyses confirmed that only having more green finance commitments is not enough to drive progress in renewables due to poor regulation. Green finance also worked well with financial development, financial markets, and the institutions involved, resulting in positive and significant effects, meaning that financial development is needed to support green finance to deliver a more effective impact on renewable energy. On the policy side, emerging economies need efforts to promote green finance as well as improve the financial system.